2011
DOI: 10.1096/fj.10-180190
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramide synthase inhibitor PDMP sensitizes chronic myeloid leukemia T315I mutant to Bcr‐Abl inhibitor and cooperatively induces glycogen synthase kinase‐3‐regulated apoptosis

Abstract: Inactivation of glycogen synthase kinase (GSK)-3 has been implicated in cancer progression. Previously, we showed an abundance of inactive GSK-3 in the human chronic myeloid leukemia (CML) cell line. CML is a hematopoietic malignancy caused by an oncogenic Bcr-Abl tyrosine kinase. In Bcr-Abl signaling, the role of GSK-3 is not well defined. Here, we report that enforced expression of constitutively active GSK-3 reduced proliferation and increased Bcr-Abl inhibition-induced apoptosis by nearly 1-fold. Bcr-Abl i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 58 publications
(73 reference statements)
0
31
0
Order By: Relevance
“…Earlier studies reported the involvement of sphingolipids such as ceramide and psychosine in the cytokine-mediated inflammatory disease of CNS, such as Krabbe disease and spinal cord injury [4][5][6][7]. Recent studies showed that PDMP increased imatinib-induced cell death in drug-sensitive and drug-resistant chronic myeloid leukemia cells via enhancing ceramide accumulation [30,31]. These data also suggest the potential utility of inhibiting GSL biosynthesis pathways in CNS disease as well as other diseases.…”
Section: Discussionmentioning
confidence: 87%
“…Earlier studies reported the involvement of sphingolipids such as ceramide and psychosine in the cytokine-mediated inflammatory disease of CNS, such as Krabbe disease and spinal cord injury [4][5][6][7]. Recent studies showed that PDMP increased imatinib-induced cell death in drug-sensitive and drug-resistant chronic myeloid leukemia cells via enhancing ceramide accumulation [30,31]. These data also suggest the potential utility of inhibiting GSL biosynthesis pathways in CNS disease as well as other diseases.…”
Section: Discussionmentioning
confidence: 87%
“…However, as our results show, both PDMP enantiomers strongly and equally reduced the ceramide content, specifically the long-chain ceramide species (≤18C), while NB-DNJ did not. At first sight, this could be surprising because D-PDMP is usually described as a ceramide-accumulating agent (Bieberich et al, 1999, Huang et al, 2011, Radin et al, 1993, Takasugi et al, 2015, Yu et al, 2012. Indeed, when blocking the conversion of ceramides to GlcCer, it could be expected that an accumulation of ceramides may have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic myeloid leukemia (CML) cell lines, increase in serine palmitoyltransferase levels via BCR/ ABL inhibition result in activation of apoptotic signals [205]. GCS inhibition in CML cell lines bearing T315I mutation results in apoptosis via activating GSK-3 [206]. Another study reported that ceramide triggers apoptosis via activating p38, caspase-8, and c-Jun N-terminal kinase (JNK) in K562 CML cells [207].…”
Section: Bioactive Sphingolipids In Apoptotic Pathwaysmentioning
confidence: 99%